Deteksi Gen Litik BRLF1 Epstein-Barr Virus pada Penderita Karsinoma Nasofaring - Tri Yulia Ningsih; Daniel Joko Wahyono; Nur Signa Aini Gumilas (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Rosenmuller fossa. Epithelial malignancy is often found in Chinese populations and Southeast Asia including Indonesia. Undifferentiated nasopharyngeal carcinoma (NPC WHO-3) type is 100% associated with Epstein-Barr virus (EBV) infection. Bam-HI R Leftward Reading Frame 1 (BRLF1) lytic gene has an important function as a transition mediator of latent phase to the lytic phase in EBV cycle. Detection of BRLF1 gene by PCR can be used for NPC diagnosis. The aim of this study is to identify BRLF1 lytic genes as molecular markers of Epstein-Barr virus in nasopharyngeal carcinoma patients with conventional PCR method and to determine the sensitivity of conventional PCR method to detect BRLF1 gene. The research design was cross sectional study. A total of 22 DNA samples were isolated from venous blood of NPC patients from RSUD Prof dr Margono Soekarjo, Purwokerto with informed consent. BRLF1 gene identification is done with conventional PCR technique. The results of this research showed that BRLF1 genes as molecular markers lytic cycle of Epstein-Barr virus in nasopharyngeal carcinoma patients can be identified conventional PCR technique that will produced DNA 157 bp. BRLF1 gene was detected in 16 samples (72.73%) of 22 samples of this study.